Efficacy of concurrent chemoradiotherapy with retrograde super selective intra-arterial infusion combined with cetuximab for synchronous multifocal oral squamous cell carcinomas - Xuefei Chen; Mitomu Kioi; Yuichiro Hayashi; Toshiyuki Koizumi; Izumi Koike; Shoji Yamanaka; Masaharu Hata; Kenji Mitsudo (Radiation Oncology, 2023)
Abstract Background The incidence of multicentric oral cancer is increasing. However, treatment encounters difficulty if each tumor needs to be treated simultaneously. The objective of this clinical case report is to highlight the effect of concurrent chemoradiotherapy with retrograde superselective intra-arterial infusion combined with systemic administration of cetuximab on synchronous multifocal oral squamous cell carcinomas. Case presentation A 70-year-old man presented to the hospital with multiple tumors and oral pain. Three independent tumors were found in the right dorsal tongue, left edge of the tongue, and left lower lip. Based on the characteristic appearance of the lesions and further evaluation, clinical diagnoses of right tongue cancer “T3”, left tongue cancer “T2” and lower left lip cancer “T1”, N2cM0 were made. Treatment was initiated with systemic administration of cetuximab, followed by intra-arterial chemoradiotherapy. Treatment results were complete response on all three local lesions, and left neck dissection was performed following the initial treatment. The patient showed no evidence of recurrence during the 4 years follow-up period. Conclusions This novel combination treatment seems to be a promising strategy for patients with synchronous multifocal oral squamous cell carcinoma.